MiR-18a and miR-17 are positively correlated with circulating PD-1+ICOS+ follicular helper T cells after hepatitis B vaccination in a chinese population - Xiaojia Xu; Yulian Li; Yaping Liang; Mingjuan Yin; Zuwei Yu; Yan Zhang; Lingfeng Huang; Jindong Ni (BMC Immunology, 2018)
Abstract Background While vaccination remains the most effective method to control hepatitis B virus (HBV) infection, 5–10% of recipients exhibit non-responsiveness to the HB vaccine. Immunological analysis of strong, weak or absent protective antibody responses to the HB vaccine should provide insights into the mechanisms that contribute to non-responsiveness. Results We investigated the potential involvement of follicular helper T (Tfh) cells in the immune response to HB vaccine, and associations between the miR-17–92 cluster and Tfh cells. We recruited 12 adults who had completed the HB vaccination course during childhood. Following a booster dose of HB vaccine, hepatitis B surface antibody (HBsAb) titers, percentage of PD-1+ICOS+ circulating Tfh (cTfh) and plasma cells, and expression of miR-17–92 were assessed at baseline (before immunization) and after vaccination on days 7 and 14. Notably, the HBsAb level gradually increased after HB vaccination while the proportion of PD-1+ICOS+ cTfh cells was significantly increased on day 7 relative to baseline, so as plasma cells. Expression of miR-18a and miR-17 within the miR-17–92 cluster and HBsAb titers in CD4+ T cells were positively correlated with the PD-1+ICOS+ cTfh cells proportions after HB vaccination. Conclusions The increase in HBsAb titers was positively associated with expression of all the components of the miR-17–92 cluster except miR-19a. Our findings indicate that the miR-17–92 cluster contributes to antibody production, and miR-18a and miR-17 are involved in Tfh cells differentiation after HB vaccination.